The internet of things and supply chains: a bibliometric analysis of emerging trends and future research directions - Ali, Abdifatah Farah; Abdullah, Rusli; Abi Hassan, Abdikarim; Abdullahi, Husein Osman; Abdullahi, Mohamed Omar (Hong Kong Success Culture Press, 2024)
This study aims to identify influential publications and authors in the field of Internet of Things (IoT) in the context of Supply Chain (SC) research through a bibliometric analysis. A search on the SCOPUS database yielded 1068 documents published between 2000 and 2023, from which the 100 most-cited articles were determined. VOSviewer was employed for bibliometric analyses, including keyword occurrences, co-authorship networks, and bibliometric coupling networks. The outcomes of the review, as well as the bibliometric examination, demonstrate the substantial interest garnered by IoT research within the SC community. The analysis revealed that China, USA, India, and the UK had the highest number of publications, while contributions from Africa were limited. Additionally, three prominent journals have extensively published on IoT, and the tenth most prolific authors have been determined. The study highlighted that SC’s IoT literature focuses on digital technology innovation, business operations, and technology optimization, information technology management, security and authentication technologies in SCs, logistics information sharing and collaboration, and technology visibility. Despite limitations such as relying on a single database (SCOPUS) and focusing on highly cited publications, this bibliometric analysis provides valuable insights into IoT in SC research. To enrich future research, it is recommended to incorporate multiple databases and consider a broader range of publications. Furthermore, given the limited number of existing bibliometric studies in into IoT in SC, further research is warranted to advance knowledge in this area.